DEVELOPING CREATIVE COMPETENCIES IN VISUAL ARTS FOR 5TH–7TH GRADE STUDENTS - Tog‘aev Keldiyor Xamidovich (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Abstract: This article explores methods for developing creative competencies in 5th–7th grade students during visual arts lessons. The study analyzes strategies that enhance students’ imagination, visual thinking, and creative skills through interactive and innovative teaching approaches. It emphasizes the importance of individual and group work, problem-based tasks, and the use of diverse artistic techniques to foster creative competencies. Practical recommendations for classroom implementation are also provided.